STRATEGI KEPALA SEKOLAH DALAM IMPLEMENTASI ADAPTIVE LEARNING PADA TRANSFORMASI PENDIDIKAN PASCAPANDEMI: (Studi Kasus di SDN 1 Nagri Kidul Purwakarta) - Ruhiat, Asep; Sukmawaty, Siska; Setiawati, Ina; Warta, Waska (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The post-pandemic era has accelerated educational transformation and encouraged schools to adopt adaptive learning approaches that are flexible, technology-based, and student-centered. This study aims to analyze the principal's strategies in implementing adaptive learning as part of educational transformation at SDN 1 Nagri Kidul Purwakarta. The study employed a qualitative approach with a case study design. Data collection techniques were designed through interviews, observations, and documentation studies focusing on school leadership, curriculum management, teacher development, and learning innovation. Data analysis referred to the interactive model of Miles, Huberman, and Saldaña. The findings indicate that adaptive learning implementation requires strategic leadership through strengthening digital infrastructure, improving teacher competence, developing flexible curriculum management, and establishing collaborative educational partnerships. The principal plays a central role in planning, organizing, directing, and controlling educational programs to ensure learning adaptation according to students' needs. The implementation of adaptive learning contributes to improving student engagement, learning effectiveness, and educational quality in the post-pandemic era. The study concludes that adaptive learning can become an effective strategy in supporting sustainable educational transformation when supported by visionary leadership, organizational readiness, and continuous professional development.